Oxytocin Ameliorates Impaired Behaviors of High Fat Diet-Induced Obese Mice - Hayashi, Ryotaro; Kasahara, Yoshiyuki; Hidema, Shizu; Fukumitsu, Satoshi; Nakagawa, Kiyotaka; Nishimori, Katsuhiko (Frontiers in Endocrinology, 2020)
Excessive intake of fat is a major risk factor for lifestyle-related diseases such as heart disease and also affects brain function such as object recognition memory, social recognition, anxiety behavior, and depression-like behavior. Although oxytocin (OXT) has been reported to improve object recognition, social recognition, anxiety behavior, and depression-like behavior in specific conditions, previous studies did not explore the impact of OXT in high-fat diet (HFD)-fed mice. Furthermore, it remains unclear whether intake of HFD affects OXT/oxytocin receptor (OXTR) in the brain. Here, we demonstrated that peripheral OXT administration improves not only social recognition but also object recognition and depressive-like behavior in HFD-fed mice. In contrast, peripheral OXT administration to HFD-fed male mice increased fear and anxiety-related behavior. In addition, we observed that intake of HFD decreased OXTR and c-fos mRNA expression in the hippocampus, specifically. Furthermore, peripheral OXT administration increased OXT mRNA expression in the hypothalamus. Altogether, these findings suggest that OXT has the potential to improve various recognition memory processes via peripheral administration but also has side effects that increase fear-related behavior in males.